Relationship of indole production and antibiotic susceptibility in the Klebsiella bacillus. - Klein, D (1975)
Of 2,442 Klebsiella strains isolated from clinical specimens at the University of Minnesota hospitals, 18.3% were found to be indole positive. A randomly selected equal number of indole-positive and indole-negative control isolates, characterized by 27 biochemical tests and by serotyping against 72 antisera, were tested against 14 antibiotics. The results indicated a greater incidence of multiple drug resistance among the indole-negative strains among those that produced indole. The organisms in the former group, in comparison to their indole-positive counterparts, were significantly more resistant to nitrofurantoin, tetracycline, chloramphenicol, neomycin, streptomycin, nalidixic acid, and kanamycin. Both groups of organisms were similar in their degree of resistance to ampicillin, carbenicillin, cephalothin, sulfisoxazole, colistimethate, polymyxin B, and gentamicin. The biochemical properties of the two indole groups were essentially identical. Correlation between serotype and multidrug resistance was inapparent.